Home security system / Jaffridin Musa and Md. Shah Mahmood - Musa, Jaffridin; Mahmood, Md. Shah (1990)
In this modern world PC is widely used for developing many kinds of control system. It is wise that a software program being made to developed a HOME SECURITY SYSTEM. The system work as a control unit to switch the alarm switches ( ON or OFF ) whenever it is required. The PC monitor will also display the house plan and at the same time shows which door or window that had been triggered. The controlling software program for this system is being written in TURBO BASIC. The normally open switches are being used as the alarm switches. An interface card (I/O CARD DMP009 ) is used to interface the computer to the alarm switches. Program is designed in such a way that the computer can received input signal from the external supply.